Early maturity of Sandfish Holothuria scabra offers more prospective broodstock supply of a commercially important aquaculture species. Issue 1 (September 2020) - Tresnati, J; Yasir, I; Syafiuddin,; Aprianto, R; Yanti, A; Bestari, A D; Tuwo, A
Abstract: The supply of broodstock is a critical limitation on aquaculture of the commercially important sea cucumber Holothuria scabra . Previous research reported that H. scabra mature at a size of more than 450 g. This size is questionable because biologically primitive organisms such as H. scabra mature relatively early. This study aimed to analyze the size at first maturity of H. scabra . The first sexual maturity was analysed by dividing the H. scabra by weight with 25 g weight class intervals, resulting in 12 weight groups. The size at first sexual maturity was determined using mature H. scabra (Stages III, IV, and V). The first maturity of H. scabra was reached at a smaller size than previously reported, from 178 H. scabra that were observed, the first sexual maturity is achieved at 42 g gutted body weight. Small H. scabra potentially used as broodstock, which will produce H. scabra seeds in hatcheries. Although small in size, H. scabra mature can reproduce, of course, with a smaller reproductive capacity. Small size at the first sexual maturity offers the potential for dramatic improvements in the procurement of broodstock stock, by providing a much more accessible supply of H. scabra prospective broodstock.